Desenvolvimento territorial rural: políticas públicas no território da cidadania do noroeste de Minas - Tanure, Tarik Marques do Prado (2012)
This dissertation studies the impacts and profiles of public policies made of different conceptions of development in the Territórios da Cidadania do Noroeste de Minas, highlighting the role due by Territórios da Cidadania Program. Two types of planning are included in the analyzed policies, the first is recorded from the 1970s, based in a centralized scope, with a strong regional inspiration and whose focus was the development of agriculture; the second occurred from mid-1990s and deepened in the 2000s, based in a decentralized planning, with territorial public policies, taking into account the peculiarities of the territory and farmers. In this sense we tried to verify which profile of public policy is best for the territory to reach the economic and social development, since it is a territory with low economic dynamism. Nevertheless, we sought to verify the initial impacts of the Territórios da Cidadania Program, analyzing whether it is still doing in practice what it set out to do. The analyzed indicators point to a substantial increase in quality of life of the territory over the period analyzed. Some of these indicators has evolved due to conjunctural factors, but a considerable part evolved, mainly because of specific public policies, particularly in the 2000s.